The Language of Self-Injury: A Data-Informed Commentary. Issue 4 (April 2021) - Hasking, Penelope A.; Boyes, Mark E.; Lewis, Stephen P.
Abstract : Abstract: Nonsuicidal self-injury (NSSI) is a behavior that can be perplexing to many people. Usually engaged as a means of regulating intense or unwanted emotions, it seems to counter the human instinct to avoid pain and harm to the self. The language people use to talk about NSSI, and individuals who engage in the behavior, can contribute to the significant stigma that is associated with NSSI. In this data-driven commentary, we report on the language clinicians and researchers typically use when talking about NSSI, and the language they consider appropriate to use. We observed some disparity in the language people use and what they deemed appropriate. Notably, researchers and clinicians report underusing terms that people with lived experience find most appropriate (someone with a history of self-injury; someone with lived experience of self-injury). We call on all researchers and clinicians to be mindful of the language they use to discuss NSSI and adopt person-centered and respectful language at all times. Abstract : Supplemental digital content is available in the text.